Survey of nutritional intake status in college baseball players - Yoko Iio; Hana Kozai; Mamoru Tanaka; Yukihiro Mori; Manato Seguchi; Yuka Aoyama; Morihiro Ito (Journal of the International Society of Sports Nutrition)
Background Diet is closely related to exercise performance. To improve athletes’ performance and manage their condition, it is important to get sufficient energy and various nutrients. Thus, it is necessary that athletes understand their nutritional intake status to improve performance and maintain health. This study aimed to explore the nutritional intake status of college baseball players using the Food Frequency Questionnaire (FFQ). Furthermore, the characteristics of their nutritional intake status with respect to athletic performance were evaluated. The result of this studyprovide an opportunity for many under-developed college athletes with irregular lifestyles to recognize and improve their nutritional problems.Methods In October 2022, a questionnaire survey of 116 male members of a college baseball club was conducted. Of whom, 100 (94.3%) members responded to the survey and 92 (92.0%) provided valid responses. The survey items included basic characteristics such as college grade and type of living arrangement, and information on living conditions, e.g. whether the participant ate breakfast. Nutritional intake was evaluated using the FFQ. Players were divided into the first (regular players in official games), second (bench players in official games), third (players who may join the second or higher team in the future), and fourth teams (players who do not belong to the first to third teams); these categories were used as a marker of performance level. The Kruskal-Wallis test was used to analyze the association between the performance levels of baseball players and the intake of each nutrient and food group obtained by the FFQ. For items that showed a significant association, inter-group comparison was performed using the Dunn-Bonferroni method.Results Carbohydrate intake was greater in the second team compared with the third and fourth teams; saturated and monounsaturated fatty acid intake was higher in the third team compared with the fourth team. Calcium, zinc, copper, manganese, insoluble dietary fiber, iodine, and molybdenum intake was higher in the second team compared with the fourth team. Intake of grains, sugar, dairy, and total energy was significantly higher in the second team compared with the fourth team. However, the protein intake ratio was significantly lower in the second team compared with the fourth team. Overall, energy deficiency and associated deficiencies in protein, fat, and carbohydrate were observed, in addition to dietary fiber and calcium deficiencies. The intake of several food groups appeared inadequate, such as potatoes, beans, vegetables, fruits, eggs, milk, and fats.Conclusions The study showed deficiencies in the amount of energy and nutrients such as protein, fat, and carbohydrate in college baseball players. Differences in the intake of carbohydrate, calcium, and insoluble dietary fiber among different performance levels were observed, with significantly higher intake of carbohydrate, calcium, and insoluble dietary fiber in the second team. Implementing organized and strategic remedial measures and athletes’ identification of nutritional problems are vital to overcome nutritional and energy deficiencies. This study provides useful information for the development of strategies to support nutritional intake in college baseball players.